Influence of the COVID-19 pandemic on the consumption of alcoholic beverages by adolescents - Serrõn da Rosa, Alice; Barni Truccolo, Adriana (Seven Editora, 2023)
The COVID-19 pandemic has brought psychosocial adjustment difficulties to many adolescents, which may favor the abusive use of alcohol. Thus, the objective of the research was to investigate whether during the COVID-19 pandemic there was a change in the amount, frequency and context of alcohol use by adolescents. For this, 253 adolescents, 124 (59%) girls, 81 (38.4%) boys and 48 adolescents who did not identify as male or female answered “other”, with a mean age of 17.33 + 0.92 years old, belonging to the high school of five schools of the state public education network, answered an online form containing short, objective and concise questions about the use, quantity, frequency and context of alcohol use before and during the pandemic of the COVID-19. The data collection instrument was adapted from the Drug Use Screening Inventory questionnaire. The results showed that approximately 43% of adolescents consumed alcoholic beverages before the onset of the COVID-19 pandemic; that for 78% of adolescents, the COVID-19 pandemic did not influence the consumption of alcoholic beverages; 24.8% reported drinking more after the start of the pandemic than before the pandemic. Regarding the context of alcohol use, approximately 40% drink with friends and 29% with family. Regarding the frequency of use, adolescents drink more on weekends and once a week. DOI: https://doi.org/10.56238/Connexpemultidisdevolpfut-087